Research from therapeutic radiographers: An audit of research capacity within the UK. Issue 2 (May 2015) - Probst, H.; Harris, R.; McNair, H.A.; Baker, A.; Miles, E.A.; Beardmore, C.
Abstract Research from Allied Health Professionals (AHPs) is anecdotally known to lag behind that of other professions. The developing research landscape within other therapies and internationally led us to question how UK practice in therapeutic radiography was developing. The aim of the survey was to audit research capacity across therapy radiography in the UK. Method An electronic survey was sent to Radiotherapy Service Managers (RSM) and research leads in each of the radiotherapy centres in the UK. An adapted version of the 'Auditing Research Capacity' tool (ARC© tool) was used as the basis of the questionnaire. Results A total of 45 RSM responded to the survey (67% response rate) and 30 Research radiographers (RR) (45% response rate). A total of 51 RR were in post equating to 40.3 whole time equivalents and averaging 1 RR per centre. Variation was evident in the commitment to the development of a research culture identified by practices such as linking research to the business planning cycle, inclusion of research in recruitment and advertising materials, or having a nominated therapeutic radiographer lead on research for the department. Over a third of responding centres did not have a research strategy and training for RRs was limited; specifically in areas such as writing funding bids, writing for publication and the research and governance process. Conclusion A number of short and long-term strategies are proposed that should enhance a positive research culture and improve research capacity for therapeutic radiography led research. These include utilisation of the existing infrastructure provided by the National Institute for Health Research, a lead or co-ordinator for research activity with a remit to motivate others. Development of links and networks, and the development of a research strategy linked to wider Trust research priorities. The research strategy should include mentoring or developing appropriate research skills for those engaged in research (including higher degree qualifications). RSMs should also encourage peer-reviewed publications, and conference presentations from all staff to ensure research results are disseminated to the wider profession.